Predialysis Cardiovascular Disease Medication Adherence and Mortality After Transition to Dialysis - Molnar, Miklos Z. (Am J Kidney Dis, 2016)
BACKGROUND: Medication non-adherence is a known risk factor for adverse outcomes in the general population. However, little is known about the association of pre-dialysis medication adherence among patients with advanced chronic kidney disease with mortality following their transition to dialysis. STUDY DESIGN: Observational study. SETTING & PARTICIPANTS: 32,348 US veterans who transitioned to dialysis during 2007–2011. PREDICTORS: Adherence to treatment with cardiovascular drugs, ascertained from pharmacy database records using proportion of days covered (PDC) and persistence during the pre-dialysis year. OUTCOMES: Post-dialysis initiation all-cause and cardiovascular mortality, using Cox models with adjustment for confounders. RESULTS: The mean age of the cohort was 72±11 (SD) years, among whom 96% were male, 74% were white, 23% were African American, and 69% were diabetic. During median follow-up of 23 (IQR, 9–36) months, 18,608 patients died. Among patients with PDC >80%, there were 14,006 deaths (mortality rate, 283 [95% CI, 278–288]/1000 patient-years [PY]); among patients with PDC >60%–80%, there were 3,882 deaths (mortality rate, 294 [95% CI, 285–304]/1000 PY); among patients with PDC ≤60%, there were 720 deaths (mortality rate, 291 [95% CI, 271–313]/1000 PY). Compared to patients with PDC >80%, adjusted HR for post-dialysis initiation all-cause mortality for patients with PDC >60%–80% was 1.12 (95% CI, 1.08–1.16) and for patients with PDC ≤60% was 1.21 (95% CI, 1.11–1.30). In addition, compared to patients showing medication persistence, adjusted HR risk for post-dialysis initiation all-cause mortality for patients with non-persistence was 1.11 (95% CI, 1.05–1.16). A similar trend was detected for cardiovascular mortality and in subgroup analyses. LIMITATIONS: Large number of missing values; the results may not be generalizable to women or the general US population. CONCLUSIONS: Pre-dialysis cardiovascular medication non-adherence is an independent risk factor for post-dialysis mortality among advanced chronic kidney disease patients transitioning to dialysis. Further studies are needed to assess whether interventions targeting adherence improve survival after dialysis initiation.